Pengaruh Gender Dan Faktor Risiko Individu Terhadap Perilaku Eskalasi Komitmen - Andhini, Mega Murti (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Escalation of commitment is the tendency of the decision maker to maintain his commitment to decisions they made in the past. Decision makers become irrational by maintaining their commitment to continue using their resources on a failed action. In financing an investment project, the escalation of commitments can harm the company and eliminate opportunities for the company to grow in the future. This study examines the effect of gender and risks on the escalation of commitment behavior. The research subjects used were 98 students of the Department of Management. This study used a 2x2 factorial experimental design between subjects. The results showed that based on gender, women tend to escalate commitments compared to men. The results of this study also concluded that individuals with risk seekers tend to increase their commitment to an incorrect decision.